The Effect Of Product Quality, Service Quality, Price On Product Purchasing Decisions On Consumer Satisfaction - Satria Mulia Chaerudin; Afriapoll Syafarudin (Yayasan Ilomata, 2021)
This study aims to provide empirical evidence regarding the influence of product quality, service quality, and price on the decision to purchase medical device products and their implications for consumer satisfaction. This study uses the PLS (Partial Least Square) analysis method. This study uses primary data in the form of a questionnaire and is distributed to 141 (one hundred and forty-one) respondents who are users of medical device products, namely apheresis machines. Based on the overall exposure of statistical calculations on structural model analysis and testing that partially, product quality is proven to have a positive and significant effect on purchasing decisions for medical device products, service quality is proven to have a positive and significant effect on purchasing decisions for medical device products, prices are proven to have a positive and significant effect. significant towards the decision-making of medical device product purchasing, product quality proved to have a positive and significant effect on consumer satisfaction of owned medical device products, service quality proved to have a positive and significant effect on consumer satisfaction of medical device products, price proved to have a positive and significant effect on consumer satisfaction of medical device products health. The purchase decision is proven to have a positive and significant effect on consumer satisfaction with medical device products.